Penentuan Nilai SPF pada Serum Fraksi Etil Asetat Ekstrak Etanol Kelopak Bunga Rosela (Hibiscus sabdarifa L.) - Nopiyanti, Vivin; Harjanti, Reslely; Aisiyah, Siti (Jurnal Farmasi (Journal of Pharmacy), 2022)
The ethyl acetate fraction of the ethanol extract of roselle flower petals (Hibiscus sabdariffa L.) was reported to have an SPF value of 13.83 ± 1.50 which was higher than the ethanol extract. So with the SPF value, the ethyl acetate fraction of roselle flower ethanol extract can be used as a sunscreen. One of the cosmetic preparations that is currently growing rapidly is serum. The purpose of this study was to formulate the ethyl acetate fraction of roselle petals into a serum that had good physical quality with variations in the concentration of xanthan gum and then the SPF value was determined. This research begins with the manufacture of ethanol extract of roselle petals. Then fractionation (liquid-liquid partition) was carried out using solvents with different polarities, namely n-hexane and ethyl acetate. Furthermore, the ethyl acetate fraction was formulated into serum with variations in the concentration of xanthan gum 0.3%, respectively; 0.6% and 1.2% were then tested for physical quality and stability. The next step is to determine the SPF value of the serum by using the UV spectrophotometric method and its calculation using the Mansur equation. The results showed that the serum ethyl acetate fraction of the ethanolic extract of roselle petals could be made into gel preparations with good physical qualities including organoleptic, viscosity, pH and homogeneity. Serum ethyl acetate fraction ethanol extract of roselle flower formulas 1, 2 and 3 had SPF values ​​F1 respectively, namely 6.8595 ± 0.08 which included moderate protection potential; F2 is 7.0089 ± 0.17; and F3 which is 8.2251 ± 0.32 with extra protection potential. Variations in the concentration of xanthan gum in the serum formula affect the physical quality of the viscosity and potency of sunscreen preparations.